Who cares what the people think? Revisiting David Miller’s approach to theorising about justice - Baderin, A; Busen, A; Schramme, T; Ulas, L; Miller, D (Palgrave Macmillan UK, 2017)
David Miller’s methodological approach to theorising about justice, articulated most explicitly in Principles of Social Justice (1999) but informing his work up to and including the recent Strangers in Our Midst (2016), takes people’s existing beliefs and sentiments – ‘what the people think’ – to play a fundamental constitutive role in the development of normative principles of justice. In this critical exchange, Alice Baderin, Andreas Busen, Thomas Schramme and Luke Ulas¸ subject differing aspects of this methodology to critique, before Miller responds.